Сравнение двух моделей миграции рассолов в подземных водах - Лю Юй (Федеральное государственное бюджетное образовательное учреждение высшего образования «Московский государственный университет им. М. В. Ломоносова», 2011)
In order to solving the task of brines migration with increasing density in fresh groundwater, a comparison is conducted between model immiscible liquid with increasing density and model of solutions migration with variable density. The example of brines propagation from the salt dump is shown the preferability of using the second model for real layered hydrogeological systems.
Keywords: МИГРАЦИЯ РАССОЛОВ; MIGRATION OF BRINE; ПЕРЕМЕННАЯ ПЛОТНОСТЬ; VARIABLE DENSITY; 556.3